HEALTH PROTOCOLS AND HEALTHY LIFESTYLE SUGGESTIONS DURING COVID-19 IN INDONESIAN MINISTRY OF HEALTH’S KOMIK SEHAT: A PRAGMATIC APPROACH - Muhammad Gani Qodratul Ihsan; Njaju Jenny Malik Tomi Hardjatno (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
The government has enforced much socialization on health protocols and healthy lifestyle implementation during Covid-19, one of them through social media by presenting comics featuring utterances of characters. Accordingly, this research explains the utterances of comic characters that represent suggestions for implementing health protocols and healthy lifestyles during Covid-19. The objective of this study is to explain the strategy of delivering comic character messages that suggest health protocols and healthy lifestyles implementation. The data used in this paper are 38 Comics strips uploaded by the Indonesian Ministry of Health in their Instagram account entitled Komik Sehat. The results showed that of the 212 illocutionary speech acts, only 40.57% of utterances conveyed messages implementation of health protocols suggestions, and 6.6% of utterances conveyed messages implementation of healthy lifestyle suggestions. Therefore, the strategy of delivering messages on recommended health protocols and healthy lifestyles through stories in Healthy Comics is not effectively carried out by the Ministry of Health of the Republic of Indonesia.